Bone loss and cartilage degeneration of the joints : diseases or normative aging processes - Plato, Chris C. (Array, 1990)
Aging represents the changes in body structure and function brought about by passage of chronological age. Aging related changes are universal and may not interfere significantly with the normal function of the individual. On the other hand, whenever these changes advance to the point where they become deleterious or significantly affect the individual's normal functions, they may be considered as diseases. To illustrate this point we discussed the two most common age related changes in the human skeleton, bone loss and cartilage degeneration in the joints. Efforts to elucidate the aetiology of both osteoporosis and osteoarthritis are oriented not only towards the study of patient clinical data, but also in the evaluation of cross-sectional, longitudinal and cross-cultural normative data